A CASE STUDY OF ENTREPRENEURSHIP COMPETITIONS TO PROMOTE ENTREPRENEURSHIP AMONG STUDENTS IN HIGHER VOCATIONAL INSTITUTIONS - Wang Juan; Marina Ibrahim Mukhtar; Noor Izwan Nasir (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
How can higher education institutions promote students’ entrepreneurial skills through entrepreneurship competitions? We provide a case study of entrepreneurship competition activities designed to boost students’ creativity and improve their entrepreneurial skills. The number of students competing in the competition, as well as the number of honours obtained for their projects, continues to grow.Through student research, we learned that students have improved their entrepreneurial ability in all aspects through the competition, which includes the ability to develop opportunities, the ability to operate and manage the business, the ability to apply professional knowledge, the ability to innovate, the ability to work in a team and manage the business, and so on, and, for some students, it also lays the groundwork for them to set up a business after participating in it. After competing in the competition, some students were able to lay the groundwork for their own businesses.